The The Importance of Building a Relationship Between Lecturers and Students for Student Satisfaction with Remote Learning - Turkiewicz, Joanna; Bęczkowska, Anna; Skrobacki, Radosław (Przegląd Badań Edukacyjnych (Educational Studies Review), 2023)
This article aimed to determine the significance of student-lecturer relationships in the context of remote learning to answer the following question: What is the relationship between student-lecturer relationships and student satisfaction with remote learning, feedback, the assessment process, lecturers’ digital competencies and students’ competencies related to remote learning? To achieve this aim, an online survey was conducted on a sample of 206 students from Milenium University in Gniezno, Poland (return rate approximately 42%) in the spring of 2022. The data were analysed through the application of mediation analysis using IBM SPSS Statistics and the Jamovi software. The main finding of the study is that the student-lecturer relationship is crucial for ensuring students’ satisfaction with remote learning. This paper contributes to the literature by explaining the potential impact of other factors on the student-lecturer relationship variable.